2013
DOI: 10.1155/2013/262685
|View full text |Cite
|
Sign up to set email alerts
|

Chinese Herbal Medicine Qi Ju Di Huang Wan for the Treatment of Essential Hypertension: A Systematic Review of Randomized Controlled Trials

Abstract: Background. Chinese herbs are potentially effective for hypertension. Qi Ju Di Huang Wan (QJDHW) is a commonly used Chinese herbal medicine as a monotherapy or in combination with other antihypertensive agents for the treatment of essential hypertension (EH). However, there is no critically appraised evidence such as systematic reviews or meta-analyses on the effectiveness and safety of QJDHW for EH. Methods and Findings. CENTRAL, PubMed, CBM, CNKI, VIP, and online clinical trial registry websites were searche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 42 publications
2
18
0
Order By: Relevance
“…TCM may be a potential option for lowering blood pressure, as TCM is capable of functioning at a system level and with various targets. Numerous review articles demonstrated that TCM administered alone or in combination with antihypertensive therapeutic agents may exert certain beneficial effects on patients with essential hypertension (3,6,8). In the present study, the YQ formula was observed to reduce MAP, which was consistent with the findings of our previous population study (12).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…TCM may be a potential option for lowering blood pressure, as TCM is capable of functioning at a system level and with various targets. Numerous review articles demonstrated that TCM administered alone or in combination with antihypertensive therapeutic agents may exert certain beneficial effects on patients with essential hypertension (3,6,8). In the present study, the YQ formula was observed to reduce MAP, which was consistent with the findings of our previous population study (12).…”
Section: Discussionsupporting
confidence: 91%
“…Certain studies have demonstrated that considerable progress has been made in lowering blood pressure using TCM (5-7). Various complementary and alternative medicine (CAM) clinical studies, including a substantial number of randomized controlled trials and systematic reviews, have shown that CAM is effective and safe for the treatment of hypertension (8)(9)(10)(11). Furthermore, our previous study showed that Liu Wei Di Huang formula, a Chinese traditional compound, moderately reduces arterial pressure in salt-sensitive hypertension in male rats (2).…”
Section: Introductionmentioning
confidence: 98%
“…As one essential aspect of TCM, Chinese herbal medicine (CHM) is widely used in Southeast Asia including Japan, South Korea, Malaysia, and Vietnam with a 3000-year-old history [29, 30]. Recently, increasing number of clinical trials and systematic reviews (SRs) have been conducted and published, and it showed that CHMs appear to be effective in lowering BP smoothly [3137]. Until now, a number of clinical trials of CHM for obesity-related hypertension have been conducted and reported with positive findings [38–42].…”
Section: Introductionmentioning
confidence: 99%
“…There are several convincing arguments for integration of these disparate systems of medicine. Integration is already helping patients with many chronic diseases [3,4], severe acute respiratory syndrome (SARS) [5], AIDS [6] and etc. Moreover, integration would be more economical for the health care system [7].…”
Section: Introductionmentioning
confidence: 99%